2016
DOI: 10.1515/jpem-2015-0333
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes analysis of radioactive iodine and total thyroidectomy for pediatric Graves’ disease

Abstract: RAI is a safe and effective option for treatment of children and adolescents with Graves' disease. In light of the rate of permanent hypoparathyroidism seen at our center with thyroidectomy and previously published long-term safety of RAI, we recommend RAI as the first line treatment for children and adolescents with Graves' disease. For those centers performing thyroidectomies, we recommend that each center select 1-2 high-volume pediatric surgeons to perform all thyroid procedures, allowing individuals to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 6 publications
1
26
0
2
Order By: Relevance
“…Some centers use RAI in pediatric patients, in which case ablative doses should be used with the aim of rapid hypothyroidism. Other side-effects are not different from those in adults [95]. RAI is contraindicated in pregnancy and during breast feeding, and conception should be postponed until at least 6 months after the therapy.…”
Section: Indications and Applied Rai Dosementioning
confidence: 98%
“…Some centers use RAI in pediatric patients, in which case ablative doses should be used with the aim of rapid hypothyroidism. Other side-effects are not different from those in adults [95]. RAI is contraindicated in pregnancy and during breast feeding, and conception should be postponed until at least 6 months after the therapy.…”
Section: Indications and Applied Rai Dosementioning
confidence: 98%
“…Eight studies reported that the thyroidectomy was performed by a high-volume surgeon [10, 11, 13-15, 21, 29, 31]. In the study by Cohen et al [23], surgery was performed by a low-volume surgeon. The remaining 13 studies did not report whether thyroidectomies were performed by a low- or a high-volume surgeon [12, 16-20, 22, 24-26, 28, 30].…”
Section: Resultsmentioning
confidence: 99%
“…In the study by Sherman et al [16], 3 patients underwent thyroidectomy after failure of RAI treatment to achieve euthyroidism. Preoperative thyroid hormone levels were reported by Cohen et al [23] and indicated hyperthyroidism (mean free T4 3.2 ng/dL [41.19 pmol/L] and mean total T3 338.7 ng/dL [5.20 nmol/L]). Patients in the study of Peroni et al [11] received preoperative preparation with Lugol’s solution and were euthyroid or hypothyroid as assessed by TSH measurement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Данные о соотношении экономической эффективности различных методов лечения БГ весьма противоречивы [91][92][93][94]. Во многих центрах 131 I назначается и детям с БГ, при этом в данном случае также рекомендуется использование аблативных активностей 131 I с целью быстрого достижения стойкого гипотиреоза [95]. Терапия 131 I противопоказана при беременности и грудном вскармливании, при этом зачатие не рекомендуется на протяжении минимум 6 месяцев после получения 131 I. Каких-либо данных о том, что терапия радиоактивным йодом сопровождается отдаленными неблагоприятными последствиями на фертильность, риск выкидышей, врожденных аномалий и мертворождения, до настоящего времени нет [96].…”
Section: показания к 131 I и его активностиunclassified